2011
DOI: 10.3899/jrheum.101143
|View full text |Cite
|
Sign up to set email alerts
|

Association of Anti-Modified Citrullinated Vimentin with Subclinical Atherosclerosis in Early Rheumatoid Arthritis Compared with Anti-Cyclic Citrullinated Peptide

Abstract: Anti-MCV was as sensitive as anti-CCP3 in diagnosing early RA. Anti-MCV testing appears to be useful for monitoring associated subclinical atherosclerosis in early RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 39 publications
(37 reference statements)
3
29
0
Order By: Relevance
“…These results are in agreement with a study, indicating that anti-CCP-positive RA patients had higher CIMT than patients without evidence of these antibodies. 47 Moreover, it has been shown that citrullinated proteins are prevalent within atherosclerotic plaques, and certain anti-CCP antibodies are correlated with the CIMT 48 and associated with the atherosclerotic burden. 49 In this sense, treatment of healthy leukocytes with anti-CCPs resulted in an elevation of cell activation markers in monocytes and neutrophils, an increase of TF expression, inflammation, and oxidative stress, indicating the participation of these autoantibodies in the development of atherosclerosis and CVD.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with a study, indicating that anti-CCP-positive RA patients had higher CIMT than patients without evidence of these antibodies. 47 Moreover, it has been shown that citrullinated proteins are prevalent within atherosclerotic plaques, and certain anti-CCP antibodies are correlated with the CIMT 48 and associated with the atherosclerotic burden. 49 In this sense, treatment of healthy leukocytes with anti-CCPs resulted in an elevation of cell activation markers in monocytes and neutrophils, an increase of TF expression, inflammation, and oxidative stress, indicating the participation of these autoantibodies in the development of atherosclerosis and CVD.…”
Section: Discussionmentioning
confidence: 99%
“…In early RA, antibodies against oxidised LDL30 and anti-modified citrullinated vimentin levels67 have been demonstrated to correlate positively with subclinical atherosclerosis. However, in the 5-year prospective study already mentioned, the incidence of overt CV events did not correlate with immunological mediators such as RF, anti-citrullinated peptide antibody and antinuclear antibodies during the first years of RA 48…”
Section: Risk Factorsmentioning
confidence: 99%
“…When all 12 studies including healthy controls were considered together [13,14,15,16,17,18,19,20,21,22,23,24], the sensitivity estimates of anti-MCV ranged from 48.4 to 89.6%, and the specificity estimates ranged from 87.2 to 100% (. Tab.…”
Section: Diagnostic Accuracies In Ra Vs Healthy Controlsmentioning
confidence: 99%
“…A previous systematic review revealed a sensitivity of 0.64-0.84 and a specificity of 0.79-0.96 for anti-MCV in the diagnosis of RA [12], but it remains unclear if the overall diagnostic values of anti-MCV antibodies are comparable to anti-CCP antibodies. Published studies on the diagnostic accuracies of anti-MCV and anti-CCP showed controversial results [13,14,15,16,17,18,19,20,21,22,23,24]. This may be due to small sample sizes, low statistical power, and/or clinical heterogeneity.…”
mentioning
confidence: 92%